Operation and Supply Chain Management - Choiril Firmansyah (Syntax Idea)
Productivity is known as the result of comparing output with input. The greater the output with minimal input, the greater the profit for the company. As a mining service company, PT GSP must be able to provide equipment in accordance with the production target given by its customers. After analyzing the design process, the next problems are that the company will still insist on using all the tools available. The next problem is how to accommodate all the tools and maximize their performance. From periodic improvement that has been done, evaluation of the results was performed and it showed a significant development. The results of the improvement on the front loading area made the delay time of the loading equipment decrease significantly as a result of the improvement and increased the productivity of the equipment significantly